Staphylococcus aureus em tonsilas de pacientes com faringotonsilite aguda recorrente: prevalência, perfil de suscetibilidade e caracterização genotípica - Cavalcanti, Veraluce Paolini (2013)
The bacterial pharyngotonsillitis are infections of the upper airways that occurs predominantly in children and adolescents. Due to the composition of the oral microbiota is difficult to clarify the role of each organism in the etiology of the disease. The presence of bacteria that produce beta-lactamase interferes with the effectiveness of beta-lactam antibiotics, the most commonly drug used in treatment of these infections, promoting the recurrence of the disease. S. aureus is one of the most common pathogen in the etiology of tonsillitis and its relevance is due to the ability of antimicrobial resistance and persistence in the tissues of the tonsils. Tonsillectomy is indicated in cases of recurrent tonsillitis after several failures in the antibiotic terapy. The aim of this study was to determine the prevalence of S. aureus in the tonsils of patients undergoing tonsillectomy, in a teaching hospital in Goiânia, the antimicrobial susceptibility profile and the genetic characterization of isolates. Tonsils obtained from 123 patients were processed, the microorganisms identified and submitted to antibiogram by conventional techniques. The isolates that presented cefoxitin resistance were submitted to tests to determine the minimum inhibitory concentration - MIC for oxacillin and to detect the presence of the mecA gene. All isolates were subjected to PCR for detection of Panton-Valentine leukocidin gene and to PFGE to determine the genetic similarity among them. It was identified 60 S. aureus isolates from 49 patients (39.8%). There were no significant difference in prevalence by sex and, the average age of male patients was lower (8.2 years) (p<0.001) than the female patients (15.3 years). Nine out 49 patients(18.4%) presented two or more different S. aureus isolates. The isolates presented resistance of 85.0%, 10.0%, 15.0%, 3.3%, 10.0%, 3.3%, 18.3% and 8.3% to penicillin, amoxicillin + ácido clavulânico, cefoxitin, ceftriaxone, erythromycin, trimethoprim/sulfamethoxazole, ciprofloxacin and tetracycline, respectively. All isolates were sensitive to linezolid and rifampin. Six erythromycin-resistant isolates (10.0%) showed inducible resistance (MLSbi) to clindamycin and quinupristin/dalfopristin. Eight isolates (13.3%) were resistant to three or more classes of antimicrobials. Despite the resistance to cefoxitin be considered a marker of the presence of the mecA gene only in two resistant isolates it has been found, xv suggesting that the cefoxitin resistance should be mediated by other mechanisms, such as the overproduction of beta-lactamases. None of these isolates showed resistance to more than two classes of antimicrobials. Among the sixty S. aureus isolates, only carried the gene encoding the Panton-Valentine leukocidin. This isolate presented resistance to five classes of antimicrobials and phenotype D. PFGE analysis grouped 36 (60,0%) of 60 isolates in 10 clusters (>80% similarity), since no one specific clone was associated with colonization of the tonsils. It was observed different patients carrying S. aureus isolates genetically identical or with a high level of similarity (>80%), suggesting in these cases, a common origin. The high prevalence of S. aureus in tonsils suggests an ability to colonize the surface and/or the persistence in the tissues of the tonsils. The isolation of MDR bacteria can promote cross-resistance to other bacteria commonly associated with recurrent tonsillitis. The results point to change the paradigm of diagnosis and treatment of recurrent tonsillitis in order to enable the correct use of antimicrobials to reduce the recurrence which is the main cause of tonsillectomy.